Seasonality and mineral, chemical and optical properties of dust storms in the Sistan region of Iran, and their influence on human health - Rautenbach, C.J. de W. (Cornelis Johannes de Wet) (University of Pretoria, 2013)
Thesis (PhD)--University of Pretoria, 2012.